The Effect of The Snowball Throwing Learning Model on Students' Learning Outcomes in The Science Subject Of Grade IV - Rini Novianti Gultom; Osco Parmonganan Sijabat; Emelda Thessalonika (CV Putra Publisher, 2026)
This research aim for know The Effect of the Snowball Throwing Learning Model on Learning Outcomes Students in the Social Sciences Subject of Class IV of UPTD Sd Negeri 122299 Pematangsiantar. Study Design utilized is design experimental pre-test post-test group Because in design This there is test in pre- test form is given before treatment and post-test were given after treatment utilizing the model. Snowballing method Based on the discussion in this chapter, the reviewer explains the study output obtained along with the formulation of the problem and the proposed hypothesis, then all study activities are discussed regarding the impact of the teaching model. The application of the Snowballing method by the learning output of the science subject in Class IV UPTD SD N 122399 Pematang Siantar is as follows: Based on the study output by the subject in Class IV UPTD SD N 122399 Pematang Siantar, the average pre-test score in the science subject